2020
DOI: 10.1126/sciadv.aaz2982
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic pathways for stress relaxation in repulsive colloidal glasses

Abstract: Residual stresses are well-known companions of all glassy materials. They affect and, in many cases, even strongly modify important material properties like the mechanical response and the optical transparency. The mechanisms through which stresses affect such properties are, in many cases, still under study, and their full understanding can pave the way to a full exploitation of stress as a primary control parameter. It is, for example, known that stresses promote particle mobility at small length scales, e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 45 publications
(51 reference statements)
8
18
0
Order By: Relevance
“…Hence, within the present study, it appears that for purely equilibrium systems a faster-thandiffusive (or exponential) dynamics cannot be observed. These findings are in agreement with recent experimental results 52 , which showed that a faster-than-exponential relaxation in colloidal glasses was related to the existence of a pre-stress condition in the samples. This in turn originates the out-of-equilibrium dynamics that is necessary for the occurrence of the anomalous dynamics.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Hence, within the present study, it appears that for purely equilibrium systems a faster-thandiffusive (or exponential) dynamics cannot be observed. These findings are in agreement with recent experimental results 52 , which showed that a faster-than-exponential relaxation in colloidal glasses was related to the existence of a pre-stress condition in the samples. This in turn originates the out-of-equilibrium dynamics that is necessary for the occurrence of the anomalous dynamics.…”
Section: Discussionsupporting
confidence: 93%
“…The ability to deform is a necessary, but not sufficient condition for the uptake and release of the stress which has been proven to be the key ingredient for the observation of an anomalous dynamics. In this context, several experimental studies, mainly on colloidal gels, have shown that the dynamics is sometimes faster than exponential [50][51][52][53][54][55] , i.e. it was observed that the intermediate scattering function F ( q, t) at a typical wavevector q can be described by a generalized exponential decay F ( q, t) ∼ exp(t/τ ) β (where τ is the relaxation time) with an exponent β greater than 1.0.…”
Section: Anomalous Dynamicsmentioning
confidence: 99%
“…Dallari et al investigated the stress relaxation in colloidal glasses [32]. They used a special sample preparation that leads to colloidal glasses with an directional built-in stress field.…”
Section: Dynamical Heterogeneities Via Two-times Correlationsmentioning
confidence: 99%
“…Recent highlights that will be addressed in this review include the observation of two types of liquid water [29] as well as probing realtime dynamics in liquid water on femto-to picosecond time scales [30,31]. Furthermore, new routes of understanding stress relaxation in glasses have been revealed recently [32]. The possibility of reaching faster time scales in a real time experiment enables the study of in-operando dynamics, e.g., ion transport in lithium batteries [33], and paves the way to sub-µs dynamics of soft matter [34,35] and biological systems [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these applications are summarized in recent reviews (Leheny, 2012;Shpyrko, 2014;Sinha et al, 2014;Madsen et al, 2016;Sandy et al, 2018). Partially driven by XPCS-applicable area detectors with increasingly high frame rates (Trapani et al, 2018;Zhang et al, 2020Zhang et al, , 2018Zinn et al, 2018;Pennicard et al, 2018;Redford et al, 2018;Maj et al, 2020;Allahgholi et al, 2019;Poikela et al, 2014) but also by emerging near-diffraction-limited storage rings (DLSRs) (Eriksson et al, 2014), a growing area of interest is XPCS applied to rapidly fluctuating and often weakly scattering soft materials (Vodnala et al, 2018;Mö ller et al, 2019;Chung et al, 2019;Zhang et al, 2019;Dallari et al, 2020;Nigro et al, 2020;Frenzel et al, 2019;Yavitt et al, 2020).…”
Section: Introductionmentioning
confidence: 99%